ANALYSIS OF EMPLOYEE WORK DISCIPLINE AT THE GENERAL ELECTION SUPERVISORY OF BONDOWOSO CITY - Dwi Solidah, Destia; Nur Rahmawati, Yeni Tri; Suheri, Suheri (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Work discipline management must be carried out properly by employees. Therefore, in the era of technology and civilization that is very advanced today, competent human resources with a high level of discipline are needed, because lack of work discipline cancause a decrease in employee performance. Unsatisfactory performance from employees will be a problem for the organization, because their work results do not meet the organization's expectations. Employee performance is very important toobserve because it is one of the keys to achieving an organization; if the organization does not carry out government activities properly, the image of the organization will be negatively affected. This study determines whether there is an influence and howsignificant is Work Discipline on Employee Performance at the Bondowoso Regency General Election Supervisory Agency Office. This study uses a quantitative approach, where this research is a method used to answer research problems related to data inthe form of numbers and statistical programs. While the type of research is descriptive research, namely describing, examining and explaining something that is studied as it is and drawing conclusions from phenomena that can be observed using numbers. The influence of Work Discipline on employee performance of 40.8% can be seen in the determination coefficient table (R Test), while 57.2% is influenced by other variables. Based on the results of the T Test, there is a significant impact or influence betweenwork discipline on employee performance. This can be seen through the results of the t-test of 3.670 and t table of 2.10092, meaning t count (3.670)> t table (2.10092), then H0 is rejected and H1 is accepted.